Comprehensive genome-wide analysis of ARF transcription factors in orchardgrass (Dactylis glomerata): the positive regulatory role of DgARF7 in drought resistance - Miaoli Wang; Wen Liu; Guangyan Feng; Gang Nie; Zhongfu Yang; Feixiang Hao; Linkai Huang; Xinquan Zhang (BMC Genomics)
Abstract Auxin response factor (ARF), a transcription factor, is crucial in controlling growth, development, and response to environmental stress. Orchardgrass (Dactylis glomerata) is an economically significant, widely cultivated forage grass. However, information on the genome-wide information and functional characterization of ARFs in orchardgrass is limited. This study identified 27 ARF genes based on the orchardgrass genome database. These DgARFs were unevenly distributed across the seven orchardgrass chromosomes and clustered into four classes. Phylogenetic analysis with multispecies of ARF proteins indicated that the ARFs exhibit a relatively conserved evolutionary path. Focusing on hormone signaling responses, DgARF7 demonstrated a potential positive regulatory role in response to 3-indole acetic acid, methyl jasmonate, gibberellin, salicylic acid, and abscisic acid signals. Additionally, exposure to drought stress induced noticeable oscillatory changes in DgARF7 gene. Notably, DgARF7 enhanced drought tolerance through heterologous expression in yeast and overexpression in Arabidopsis. Overexpressed Arabidopsis lines of DgARF7 exhibited a markedly higher relative water content and superoxide dismutase activity, while the malondialdehyde content was significantly decreased compared to wild type under drought stress. DgARF7 also accelerated flowering time by inducing the flowering-related gene expression levels in Arabidopsis. This research provides important insights into the role of DgARF7 in orchardgrass and provides further understanding in molecular breeding.